Differential responses to acute administration of a new 5-HT7-R agonist as a function of adolescent pre-treatment: phMRI and immuno-histochemical study - Altabella, Luisa; Sbriccoli, Marco; Zoratto, Francesca; Poleggi, Anna; Vinci, Ramona; Lacivita, Enza; Leopoldo, Marcello; Laviola, Giovanni; Cardone, Franco; Canese, Rossella; Adriani, Walter (Frontiers in Behavioral Neuroscience, 2014)
LP-211 is a new, selective agonist of serotonin (5-hydroxytryptamine, 5-HT) receptor 7 (5-HT7-R), which is part of a neuro-transmission system with a proposed role in neural plasticity and in mood, cognitive or sleep regulation. Adolescent subchronic LP-211 treatment produces some persisting changes in rats’ forebrain structural and functional parameters. Here, using pharmacological MRI (phMRI), we investigated the effect of acute administration with LP-211 (10 mg/kg i.p.), or vehicle, to adult rats previously exposed to the same drug (0.25 mg/kg/day for 5 days), or vehicle, during adolescence (44 to 48 post-natal days); histology and immuno-histochemistry were performed ex vivo to evaluate neuro-anatomical and physiological long-term adaptation to pharmacological pre-treatment. The phMRI signal reveals forebrain areas (i.e. hippocampus, orbital prefrontal cortex), activated in response to LP-211 challenge independently of adolescent pre-treatment. In septum and nucleus accumbens, sensitized activation was found in adolescent pre-treated rats but not in vehicle-exposed controls. Immuno-histochemical analyses showed marked differences in septum as long-term consequence of the adolescent pre-treatment: increased level of 5-HT7-R, increased number of 5-HT7-R positive cells, and enhanced astrocyte activation. For nucleus accumbens, immuno-histochemical analyses did not reveal any difference between adolescent pre-treated rats and vehicle-exposed controls. In conclusion, subchronic LP-211 administration during adolescence is able to induce persistent physiological changes in the septal 5-HT7-R expression and astrocyte response that can still be observed in adulthood. Data shed new insights into roles of 5-HT7-R for normal and pathologic behavioral regulations.